Low-voltage diode-R current squarer circuit - Boonchu, Boonchai; Surakampontorn, Wanlop (My University, 2019)
In this paper, a Diode-R squaring circuit cell is presented. It is then employed to realize a new current squarer circuit that suitable for implemented in BJT technology. The design configuration is through the combination of a simple current mirror and a current inverter circuit. The proposed current squarer can operate for input current of ±19 μA, with the harmonic distortion of about 1.886%. Furthermore, its features low voltage of 1.5 V single power supply and 0.42 mW power consumption. The SPICE simulation results are used to confirm the performance of the circuit and the validity of the design technique.
Keywords: Current inverter; Current mirror; Diode-R squaring circuit; Low-voltage circuit; Squarer